Nakuru : an African town = Nakuru : stad in Afrika - Jiroflée, Karin; de Meulder, Bruno; Heynen, Hilde; Loeckx, André (Leuven: Stad Leuven; KU Leuven, 1998)
"Inleiding : Karin Jiroflée ; redactie/editing by : Bruno De Meulder, Hilde Heynen, André Loeckx,... et al."